TEACHER'S TYPE OF QUESTIONS AND QUESTIONING BEHAVIOR IN EFL CLASSROOM : A Case Study of an English Teacher at a Public Senior High School in Bandung - Verra Aprilianty Mutohariatul Suhendar, - (2018)
The study was conducted to identify the types of questions used in the EFL classroom. Since every question serves a different function in language learning, this research also examines the reason why certain questions are asked in the classroom. The last purpose of this study is to find out students' responses on teacher's question. To meet the purposes, this study employed a descriptive qualitative research design. The study was carried out by observing and taking video recordings of an eleventh grade English teacher at a Senior High School in Bandung. An interview was also employed in this study. The collected data were analyzed by using Long and Sato (1983)'s classification of display and referential question. The findings indicate that in the question type, display questions were highly uttered by the teachers rather than referential questions. As the purposes of learning English in a senior high school context is to engage students to communicate in spoken and written language, all the questioning functions are related to eliciting information, checking students' understanding, and encouraging them to participate more in the classroom. Moreover, the findings of this study reveal that the use of display question does not really provoke students to give long answers by using the target language. However, when it comes to referential question, students gave longer answer. The longest answer form the students was more than four words. Finally, the results of this study would be of help in teacher training programs. This can be achieved by means of emphasizing the importance of questions and the questioning skill and the role that they play in students' success.;---Penelitian ini dilakukan untuk mengidentifikasi jenis-jenis pertanyaan yang digunakan oleh guru di dalam kelas EFL. Sejak setiap pertanyaan memiliki perbedaan fungsi dalam pembelajaran bahasa, penelitian ini juga menguji alasan digunakannya pertanyaan di dalam kelas. Tujuan terakhir diadakannya penelitian ini adalah untuk menemukan respon siswa terhadapa pertanyaan guru. Untuk mencapai tujuan, penelitian ini menganut metode deskripsi kualitatif. Penelitian ini dilakukan dengan mengamati dan mengambil rekaman video dari seorang guru bahasa Inggris kelas sebelas sekolah menengah atas di Bandung. Interview pun dilakukan dalam penelitian ini. Data yang telah dikumpulkan kemudian dianalisis berdasarkan klasifikasi pertanyaan oleh Long dan Sato (1983). Hasil dari penelitian menunjukan bahwa display question lebih banyak digunakan oleh guru daripada referential question. Sebagaimana tujuan dari pembelajaran bahasa Inggris dalam konteks sekolah menengah atas adalah untuk berkomunikasi dalam bentuk ucapan dan juga tulisan, seluruh fungsi dari pertanyaan mencakup memperoleh informasi, memeriksa pemahaman peserta didik, dan mendorong mereka untuk lebih banyak ikut serta dalam kelas. Selanjutnya, penemuan dari penelitian ini mengungkapkan bahwa penggunaan display question tidak merangsang siswa untuk menghasilkan bahasa sasaran dengan jumlah banyak. Namun pada referential question, peserta didik memberikan jawaban yang lebih panjang. Jawaban terpanjang siswa dapat mencapai lebih dari empat kata.